Customized humanoptics silicone iris prosthesis in eyes with posttraumatic iris loss: outcomes and complications. (25th January 2016) - Spitzer, Martin Stephan; Nessmann, Anja; Wagner, Julia; Yoeruek, Efdal; Bartz‐Schmidt, Karl Ulrich; Szurman, Peter; Szurman, Gesine B.
Abstract: Purpose: Posttraumatic partial or total iris defects often cause significant debilitating glare, photophobia, decreased vision and cosmetic problems. Currently, the best cosmetic results can be obtained with a customized silicone iris prosthesis. However, little is known about the functional results and the rate of complication if this type of iris prosthesis is implanted into severely traumatized eyes. The aim of this study is to analyse the functional and cosmetic outcomes as well as complications after Artificial Iris implantation. Methods: A consecutive series of 34 patients who received a customized silicone iris prosthesis after severe globe injury with total or sub‐total iris loss was analysed retrospectively. Additionally, patients were interviewed regarding change in subjective complaints. Results: Median follow‐up was 24 months (range 12.0–48.8). Mean visual acuity prior to Artificial Iris implantation was 1.1 logMAR (range 0.3–2.6). Five patients (15%) had pre‐existing glaucoma and eight patients (24%) had pre‐existing hypotony. Visual acuity 12 months after surgery was 1.4 logMAR (range 0.2–2.6). Complications included newly diagnosed glaucoma in three eyes (9%) and hypotony in three eyes (9%), persisting intraocular inflammation or macular oedema in seven patients (21%), and corneal endothelial decompensation requiring corneal transplantation in six patients (18%). Patients' satisfaction increased by reducing glare and enhanced cosmetic appearance. Conclusion: The customized silicone iris prosthesis is an individualized treatment approach with appealing cosmetic results. Therefore, especially traumatized eyes with highly different posttraumatic conditions could benefit. However, in some patients, the implantation of this device may cause an increase of intraocular pressure, corneal endothelial decompensation or persisting inflammation.